Evidence of Severe Acute Respiratory Syndrome Coronavirus 2 Reinfection After Recovery from Mild Coronavirus Disease 2019. (21st November 2020) - Lee, Jee-Soo; Kim, So Yeon; Kim, Taek Soo; Hong, Ki Ho; Ryoo, Nam-Hee; Lee, Jaehyeon; Park, Jae Hyeon; Cho, Sung Im; Kim, Man Jin; Kim, Young-gon; Kim, Boram; Shin, Ho Seob; et al.
Abstract: Background: Positive results from real-time reverse-transcription polymerase chain reaction (rRT-PCR) in recovered patients raise concern that patients who recover from coronavirus disease 2019 (COVID-19) may be at risk of reinfection. Currently, however, evidence that supports reinfection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has not been reported. Methods: We conducted whole-genome sequencing of the viral RNA from clinical specimens at the initial infection and at the positive retest from 6 patients who recovered from COVID-19 and retested positive for SARS-CoV-2 via rRT-PCR after recovery. A total of 13 viral RNAs from the patients' respiratory specimens were consecutively obtained, which enabled us to characterize the difference in viral genomes between initial infection and positive retest. Results: At the time of the positive retest, we were able to acquire a complete genome sequence from patient 1, a 21-year-old previously healthy woman. In this patient, through the phylogenetic analysis, we confirmed that the viral RNA of positive retest was clustered into a subgroup distinct from that of the initial infection, suggesting that there was a reinfection of SARS-CoV-2 with a subtype that was different from that of the primary strain. The spike protein D614G substitution that defines the clade "G" emerged in reinfection, while mutations that characterize the clade "V" (ie, nsp6 L37F and ORF3a G251V) were present at initial infection. Conclusions: Reinfection with a genetically distinct SARS-CoV-2 strain may occur in an immunocompetent patient shortly after recovery from mild COVID-19. SARS-CoV-2 infection may not confer immunity against a different SARS-CoV-2 strain. Abstract : We conducted serial whole-genome sequencing of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Our results highlight possible SARS-CoV-2 reinfection with a genetically distinct SARS-CoV-2 strain in patients shortly after recovery from mild coronavirus disease 2019 (COVID-19).